Gratifying Ambiguity: Psychological Processes Leading to Enjoyment and Appreciation of TV Series with Morally Ambiguous Characters. Issue 5 (3rd September 2019) - Meier, Yannic; Neubaum, German
Abstract : Morality plays an integral role in perceiving and judging fictional characters since liking morally good characters leads to a general enjoyment of the narrative if the outcomes of actions are favorable for the liked character. However, some fictional characters frequently violate moral standards but are still popular at the same time. To explain this paradox, the present study offers a two-process model on the appeal of morally ambiguous characters, proposing psychological mechanisms leading to either enjoyment or appreciation. These mechanisms were tested based on an online survey ( N = 429) examining four different television series which featured morally ambiguous protagonists. Findings largely supported the notion that while liking the character leads to enjoyment, social comparison processes (based on moral principles) were associated with appreciation. This study extends findings of previous investigations by offering a more comprehensive understanding of how morally complex narratives can lead to entertainment experiences.